Understanding reactions to an internet-delivered health-care intervention: accommodating user preferences for information provision - Yardley, Lucy (BioMed Central, 2010)
BACKGROUND: It is recognised as good practice to use qualitative methods to elicit users' views of internet-delivered health-care interventions during their development. This paper seeks to illustrate the advantages of combining usability testing with 'theoretical modelling', i.e. analyses that relate the findings of qualitative studies during intervention development to social science theory, in order to gain deeper insights into the reasons and context for how people respond to the intervention. This paper illustrates how usability testing may be enriched by theoretical modelling by means of two qualitative studies of users' views of the delivery of information in an internet-delivered intervention to help users decide whether they needed to seek medical care for their cold or flu symptoms. METHODS: In Study 1, 21 participants recruited from a city in southern England were asked to 'think aloud' while viewing draft web-pages presented in paper format. In Study 2, views of our prototype website were elicited, again using think aloud methods, in a sample of 26 participants purposively sampled for diversity in education levels. Both data-sets were analysed by thematic analysis. RESULTS: Study 1 revealed that although the information provided by the draft web-pages had many of the intended empowering benefits, users often felt overwhelmed by the quantity of information. Relating these findings to theory and research on factors influencing preferences for information-seeking we hypothesised that to meet the needs of different users (especially those with lower literacy levels) our website should be designed to provide only essential personalised advice, but with options to access further information. Study 2 showed that our website design did prove accessible to users with different literacy levels. However, some users seemed to want still greater control over how information was accessed. CONCLUSIONS: Educational level need not be an insuperable barrier to appreciating web-based access to detailed health-related information, provided that users feel they can quickly gain access to the specific information they seek.